Long-term results of surgically-assisted maxillary protraction - Nevzatoğlu Şirin; Küçükkeleş Nazan (Sciendo, 2014)
Objective: The long-term treatment results of surgically-assisted facemask therapy were assessed by a comparison of the immediate protraction effects with those seen at five years review.